Literature Review: Tren Penelitian Pengembangan Media Pembelajaran Bahasa Arab Berbasis Canva di Indonesia - Adhama, Hanif Bimo; Hikmah, Khizanatul (STIQ Amuntai, 2025)
This study aims to identify and analyze research trends in the development of Arabic language learning media based on the Canva application in Indonesia from 2019 to 2024. The method employed is a Systematic Literature Review (SLR) following the PRISMA guidelines, using the Publish or Perish software to retrieve relevant scientific publications from the Google Scholar database. After applying inclusion and exclusion criteria, 16 articles were selected for descriptive and visual analysis. The findings reveal a significant increase in publication numbers in 2024. The most commonly developed media was presentation-based media, with a primary focus on enhancing speaking skills (maharah kalam). Furthermore, the most frequently used research methodology was Research and Development (R&D). These results highlight Canva as a promising, innovative, and effective tool for Arabic language teaching across various educational levels in Indonesia. This study is expected to contribute both theoretically and practically to the field of digital-based learning media and to serve as a valuable reference for future research in related areas.